Does globalization affect regional growth? Evidence for NUTS-2 regions in EU-27 - Wolfgang Polasek; Richard Sellner (Institute for Advanced Studies (IHS), 2011)
We analyze the influence of newly constructed globalization measures on regional growth for the EU-27 countries between 2001 and 2006. The spatial Chow-Lin procedure, a method constructed by the authors, was used to construct on a NUTS-2 level a complete regional data for exports, imports and FDI inward stocks, which serve as indicators for the influence of globalization, integration and technology transfers on European regions. The results suggest that most regions have significantly benefited from globalization measured by increasing trade openness and FDI. In a non-linear growth convergence model the growth elasticities for globalization and technology transfers decrease with increasing GDP per capita. Furthermore, the estimated elasticity for FDI decreases when the model includes a higher human capital premium for CEE countries and a small significant growth enhancing effect accrues from the structural funds expenditures in the EU. - regional globalization measures ; EU integration (structural funds) ; regional growth convergence models ; foreign direct investment (FDI)
Keywords: C11; C15; C51; R12; 330